Utilizing PacBio Iso-Seq for novel transcript and gene discovery of abiotic stress responses in Oryza sativa L. - Schaarschmidt, Stephanie; Fischer, Axel; Lawas, Lovely Mae F.; Alam, Rejbana; Septiningsih, Endang M.; Bailey-Serres, Julia; Jagadish, Krishna S.V.; Huettel, Bruno; Hincha, Dirk K.; Zuther, Ellen (MDPI, 2020)
The wide natural variation present in rice is an important source of genes to facilitate stress tolerance breeding. However, identification of candidate genes from RNA-Seq studies is hampered by the lack of high-quality genome assemblies for the most stress tolerant cultivars. A more targeted solution is the reconstruction of transcriptomes to provide templates to map RNA-seq reads. Here, we sequenced transcriptomes of ten rice cultivars of three subspecies on the PacBio Sequel platform. RNA was isolated from different organs of plants grown under control and abiotic stress conditions in different environments. Reconstructed de novo reference transcriptomes resulted in 37,500 to 54,600 plant-specific high-quality isoforms per cultivar. Isoforms were collapsed to reduce sequence redundancy and evaluated, e.g., for protein completeness (BUSCO). About 40% of all identified transcripts were novel isoforms compared to the Nipponbare reference transcriptome. For the drought/heat tolerant aus cultivar N22, 56 differentially expressed genes in developing seeds were identified at combined heat and drought in the field. The newly generated rice transcriptomes are useful to identify candidate genes for stress tolerance breeding not present in the reference transcriptomes/genomes. In addition, our approach provides a cost-effective alternative to genome sequencing for identification of candidate genes in highly stress tolerant genotypes.